Quadratic Zeeman Effect for an s-electronMoving in a Screened Coulomb Potential - Kassim, H. (Iraqi Journal of Science, 2025)
The s-level of a screened hydogenic atom in a uniform magnetic field of arbitrary strength B have been calculated accurately. First, the related spherical symmetric case )~(2122Brhas been treated by using the linear variational method. The trial wave function is taken as linear mixture of hydogenic and 3D harmonic ascillator wave functions of s-symmetry. Second, the actual nonspherical case)(21222yx is studied by adopting the correction proposed by Mustafa and Chhajlany (Phys. Rev.A,50,(I994),2926). The latter accounts for the difference between the two cases in an appaximate way by utilizing the properties of the 2D and 3D harmonic oscillators.We start our study with the unsceened hydrogen case to recover their shifted N1results and deal then with the more involved case of the screened hydrogen atom covering wide ranges of the applied field and of the screening length.